Пути Перехода к Устойчивой Энергетике - United Nations (United Nations, 2020)
Energy underpins the development of economies and most of the goals and targets of the 2030 Agenda. The energy sector plays a critical role in finding solutions for both sustainable development and climate change mitigation. Since the universal agreement on the seventeen Sustainable Development Goals (SDGs) including the goal on sustainable energy SDG 7 in 2015, countries have commenced with the implementation of the 2030 Agenda. However, at this stage, there is a gap between the agreed energy and climate targets and the strategies and systems that are being put in place today to achieve them. Accelerated and more ambitious strategies and policies will be needed to fill the persistent gaps to achieve the 2030 Agenda.